Dulcie Holland interviewed by Hazel de Berg in the Hazel de Berg collection - Holland, Dulcie, 1913-2000.; De Berg, Hazel, 1913-1984. (1975)
Holland speaks of her musical studies at the Sydney Conservatorium and at the Royal College in London ; her composing career and method of work ; the importance of melody ; writing music for children ; writing music for films ; writing a history of music with her husband Alan Bellhouse.
Also available online
Related material : Papers of Dulcie Holland held by National Library of Australia Manuscripts Section at MS 6853.
Timed summary (2 p.) and transcript (20 leaves)
Keywords: Holland, Dulcie, -- 1913-2000 -- Interviews; Composers -- Australia -- Archives; Pianists -- Australia -- Archives; Women composers -- Australia -- Interviews; Composers; Pianists